Spontaneous seizures after ECT in a patient medicated with bupropion, sertraline and risperidone - Doellinger,Orlando von (2016)
Abstract Objective: To report a case of post-electroconvulsive therapy spontaneous seizures in a patient medicated with sertraline, bupropion and risperidone. Case description: A 53-year-old woman with recurrent major depression was admitted to our psychiatry department for a major depressive episode of 6 weeks' duration, with psychotic symptoms. She was already on 200 mg/day of sertraline and 2 mg/day of risperidone. After 8 weeks on 200 mg/day of sertraline, 4 mg/day of risperidone and slow release bupropion (titrated to 300 mg/day), with no objective improvements, the decision was taken to initiate a course of 8-10 electroconvulsive therapy (ECT) sessions. Two days after the first treatment, three generalized tonic-clonic seizures occurred within 6 hours. Phenytoin and sodium valproate were added to the patient's daily medication and no further spontaneous seizures were observed. After neurologic assessment and discussion of the case, phenytoin and bupropion were withdrawn at once (two days after the spontaneous seizures) and the decision was taken to resume the ECT treatment. No further spontaneous seizures occurred and, at discharge, the patient exhibited significant improvements and was free from major depressive symptoms. Comments: This report illustrates a case of post-ECT spontaneous seizures that might have been due to a specific pharmacological etiological pathway, namely, bupropion's proconvulsive properties, although both sertraline and risperidone also lower the convulsive threshold.